THE INFLUENCE OF EMPLOYEES' ENGLISH SKILLS TO THEIR WORK PERFORMANCE (A STUDY CASE AT REGIONAL OFFICE FOR CULTURAL PROPERTIES PRESERVATION IN SOUTH SULAWESI - Khoiriyatul Annisa; Seny Luhriyani; Andi Samtidar (International Journal of Business English and Communication, 2023)
English is broadly used as a lingua franca to talk amongst overseas travelers, in other term, it's far referred as global language. Undeniably, communication skills especially in English are very important for employees in the workplace, especially for those who work in the tourism industry. And English is one of the essential factors to improve tourism industry. After noting the widespread influence of English skills in the world of work, especially in tourism. The writer took the research entitled “The Influence of Employees’ English Skills to Their Work Performance (A Study Case at Regional Office for Cultural Properties Preservation in Sulawesi)”. The purpose of this study was to find out whether or not there is an influence of English skills on employees’ performance at the Regional Office for Cultural Properties Preservation in South Sulawesi. This study is qualitative research using the descriptive approach to describe the object of the research without any interference from the researcher. The data collection techniques used in this study were observation and interviews. This study shows that the employees’ English skills were still lacking. However, the employees still used English at every chance they get. In addition, the employees use English to serve foreign tourists who come to visit, handle incoming letters, make leaflets and other media, make publications, understand texts in English, and translate a book from Indonesian to English and vice versa. In addition, translator applications or websites, such as Google Translate, are often used by employees to help them do their assignments. Furthermore, it was also found that the use of English has influenced employees’ performance, English can help them in completing their work. Therefore, it is suggested that the Regional Office for Cultural Properties Preservation in South Sulawesi, especially the Public Service and Publication working group conduct English language training for employees.